Deciphering long-term records of natural variability and human impact as recorded in lake sediments: a palaeolimnological puzzle - Mills, Keely; Schillereff, Daniel; Saulnier-Talbot, Émilie; Gell, Peter; Anderson, N. John; Arnaud, Fabien; Dong, Xuhui; Jones, Matthew; McGowan, Suzanne; Massaferro, Julieta; Moorhouse, Heather; Perez, Liseth; et al. (Wiley, 2016)
Global aquatic ecosystems are under increasing threat from anthropogenic activity, as well as being exposed to past (and projected) climate change, however, the nature of how climate and human impacts are recorded in lake sediments is often ambiguous. Natural and anthropogenic drivers can force a similar response in lake systems, yet the ability to attribute what change recorded in lake sediments is natural, from that which is anthropogenic, is increasingly important for understanding how lake systems have, and will continue to function when subjected to multiple stressors; an issue that is particularly acute when considering management options for aquatic ecosystems. The duration and timing of human impacts on lake systems varies geographically, with some regions of the world (such as Africa and South America) having a longer legacy of human impact than others(e.g. New Zealand). A wide array of techniques (biological, chemical, physical and statistical) is available to palaeolimnologists to allow the deciphering of complex sedimentary records. Lake sediments are an important archive of how drivers have changed through time, and how these impacts manifest in lake systems. With a paucity of ‘real‐time’ data pre‐dating human impact, palaeolimnological archives offer the only insight into both natural variability (i.e. that driven by climate and intrinsic lake processes) and the impact of people. Whilst there is a need to acknowledge complexity, and temporal and spatial variability when deciphering change from sediment archives, a palaeolimnological approach is a powerful tool for better understanding and managing global aquatic resources.